Comparative effects of final canal irrigation with chitosan and EDTA (Journal of Applied Oral Science, 2021)
Chitosan is a natural, biocompatible chelating substance with potential for dental use. This study compared the effects of final canal irrigation with chitosan and EDTA on dentin microhardness, sealer dentin tubules penetration capacity, and push-out strength. Methodology: Fifty canine roots were distributed according to the final irrigation protocol (n=10): G1- 15% EDTA with conventional irrigation; G2- 15% EDTA with Endovac; G3- 0.2% chitosan with conventional irrigation; G4- 0.2% chitosan with Endovac; and G5- without irrigation. Specimens were obturated (AH Plus) and sectioned in 3 slices per root third. The first slice was used for microhardness and sealer penetration assessments under a laser confocal microscope. The second was utilized in a push-out strength test. The third slice was discarded. Data were analyzed using 2-way ANOVA and Tukey's post hoc test (α<0.05). Failure mode was determined at x40 magnification. Results: Microhardness reduction was more significant in groups G2 and G4 (p<0.05). Sealer penetration through dentin was significantly greater in group G2 (p<0.05). There was no significant difference between groups G1, G3, and G4 (p>0.05). In general, all experimental groups presented similar bond resistance (p>0.05) that significantly differed from the control (p<0.001). Mixed type failures were predominant. Conclusions: In general, 0.2% chitosan and 15% EDTA solutions act in a similar manner with regard to the variables studied. The use of Endovac potentiates the effect of these solutions.